Adverse event profiles of adjuvant treatment with opicapone in Parkinson’s disease: A systematic review and meta-analysis - Xie, Luwen; Qi, Xiaoyi; Wang, Xuan; He, Bing; Wang, Yu; Zhang, Wei; Yu, Zehui; Deng, Mingming; Liang, Sicheng; Lü, Muhan (Frontiers in Pharmacology, 2022)
Background: Opicapone, a novel third-generation catechol-O-methyltransferase inhibitor, has demonstrated efficacy in Parkinson's Disease (PD) patients with end-of-dose motor fluctuations. Objective: This study aimed to compare the short-term (< 6 months) and long-term (≥ 6 months) tolerability of opicapone adjuvant treatment in PD patients. Method: Electronic databases including PubMed, Embase, Web of Science and Cochrane library were searched for randomized controlled trials (RCTs) and observational studies. The end points included any treatment-related adverse events (TEAEs), serious TEAEs (SAEs) and treatment discontinuation. A random-effects model was used to generate overall incidences of TEAE. Results: Three RCTs, three RCT extension studies and three open-label studies involving 2177 PD patients were evaluated. In the short-term studies, there were reports of TEAEs with an incidence of ≥ 5% in individuals treated with opicapone 50 mg, including dyskinesia (14.1%), elevated blood creatine phosphokinase levels (8.0%) and urinary tract infection (6.0%). Any TEAEs, SAEs and treatment discontinuation all occurred at rates of 62.9%, 4.8% and 9.3%, respectively. TEAEs with opicapone 50 mg that were reported by more than 5% of patients in long-term studies included dyskinesia (16.1%), dry mouth (12.1%), medication effect decreased (12.1%), PD exacerbated (7.8%), blood creatine phosphokinase level raised (7.4%), nausea (6.1%) and insomnia (5.1%). The incidence of any TEAEs, SAEs and treatment discontinuation were, correspondingly, 73.2%, 8.7% and 8.4%. Conclusion: These studies demonstrated that opicapone was generally well-tolerated and had a low risk of adverse events, suggesting that it could be a valuable therapeutic choice for people with PD.